The Art of Semiparametrics - Sperlich, Stefan; Aydinli, Gökhan (Contributions to Statistics, 2006)
This selection of articles has emerged from different works presented at the conference "The Art of Semiparametrics" celebrated in 2003 in Berlin. The idea was to bring together junior and senior researchers but also practitioners working on semiparametric statistics in rather different fields. The meeting succeeded in welcoming a group that presents a broad range of areas where research on, respectively with, semiparametric methods is going on. It contains mathematical statistics, econometrics, finance, business statistics, etc. and thus combines theoretical contributions with more applied and partly even empirical studies. Although each article represents an original contribution to its own field, they all are written in a self-contained way to be read also by non-experts of the particular topic. This volume therefore offers a collection of individual works that together show the actual large spectrum of semiparametric statistics.